2007
DOI: 10.1016/j.ijid.2006.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Infectious pathogens in volunteer and replacement blood donors in Pakistan: a ten-year experience

Abstract: The frequency of hepatitis C amongst Pakistani donors is the highest in the region while that of hepatitis B is declining gradually. Volunteer donors have lower frequencies of tested infections compared to replacement donors. Compared to neighboring India, syphilis occurs with a similar frequency but HIV is seen less commonly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
6
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 11 publications
8
47
6
4
Order By: Relevance
“…Indeed, one subject is more likely to have HBV that he is older and HBs Ag persists long after the infection. This result is found in other studies [4,26].…”
Section: Seroprevalency Of Transfusion-transmissible Infections In Rdsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, one subject is more likely to have HBV that he is older and HBs Ag persists long after the infection. This result is found in other studies [4,26].…”
Section: Seroprevalency Of Transfusion-transmissible Infections In Rdsupporting
confidence: 91%
“…80% of these have admitted that they had this behavior to be sure that the blood needs of their parents are insured [3]. Others have suggested the possibility that some RD may be paid donors submitted by the patient's family members as RD [4]. In volunteer donors, the main motivation to make a donation is altruism [5][6][7][8], which makes them safer donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 5% of infants obtained HCV infection transmitted from a mother carrying both HCV antibody and HCV RNA [32] ; four studies in pregnant women showed the percent prevalence to be 4.54% ± 3.5% [33][34][35][36] . Volunteer blood donors are the healthiest population in a community and HCV prevalence in these individuals is a true reflector of a general population's health [9] ; twelve different studies showed the percent prevalence to be 3.78% ± 0.41% in blood donors [17,[37][38][39][40][41][42][43][44][45][46][47] .…”
Section: General Populationmentioning
confidence: 99%
“…Mujeeb et al [37] , 1996 Karachi EIA 839 2.40 Bhatti et al [38] , 1996 Rawalpindi EIA 760 4.80 Mujeeb et al [39] , 2000 Karachi ELISA 7047 2.40 Ali et al [40] , 2003 Quetta ELISA 1500 1.87 Asif et al [41] , 2004 Islamabad MEIA 3430 5.14 Ahmad et al [42] , 2004 Peshawar MEIA 4000 2.20 Zaidi et al [43] , 2004 Peshawar ELISA 49 037 2.60 Chaudry et al [44] , 2005 Lahore ELISA 890 6.06 Abdul Mujeeb et al [45] , 2006 Karachi ELISA 7325 3.60 Chaudhary et al [17] , 2007 Rawalpindi MEIA 1428 2.52 Sultan et al [46] , 2007 Different Areas EIA 41 498 4.99 Khattak et al [47] , 2008 Different Areas ELISA 103 858 4 IDU Kuo et al [52] , 2006 Lahore ELISA 351 88 Achakzai et al [53] , 2007 Quetta ELISA 50 60 Altaf et al [54] , 2009 Karachi ELISA 161 94 Platt et al [55] , 2009 Abbottabad ELISA 102 8 Platt et al [55] , 2009 Rawalpindi ELISA 302 17.30 Thalassemic Bhatti et al [58] , 1995 Rawalpindi ELISA 35 60 Muhammad et al [59] to HCV infection than who did not receive injection [78] . Khan et al [74] reported that if both oral and injectable medicine were equally effective, 44% of the Pakistani population preferred injectable medicine.…”
Section: Blood Donorsmentioning
confidence: 99%